PERLINDUNGAN HUKUM TERHADAP SISWA KORBAN KEKERASAN SEKSUAL OLEH OKNUM GURU SMP DI TINJAU DARI PASAL 54 AYAT (1) UU NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Sukmawati Rahayu; R. Eriska Ginalita Dwi Putri (INTELIGENSIA MEDIA, 2024)
This research aims to find out how legal efforts are given in handling cases of sexual violence committed by unscrupulous teachers in the school environment and to find out the considerations of the Panel of judges in deciding the case in case number 123/Pid.Sus/2023/PN SKB. The method used in this research is a qualitative method. The type of research used by the author is normative juridical research. The data collection technique in this research is literature study with the main data source is the criminal law code. The results showed that the perpetrator was guilty of committing an act of sexual violence against a minor victim in an educational unit environment where the perpetrator was declared a subject teacher at a junior high school (Sekolah Menengah Pertama) who should protect his students to gain knowledge in an educational unit environment, this case violated Article 82 paragraph (2) of Indonesian Law No. 17 of 2016 concerning the Stipulation of Government Regulations in Lieu of Law no. 1 of 2016 concerning the Second Amendment to the Law on Education. 1 of 2016 concerning the Second Amendment to Law No. 23 of 2002 concerning Child Protection into Law Jo Article 76E of Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection jo Article 65 paragraph 1 of the Criminal Code, as well as the decision made by the panel of judges did not refer to the Law which states that a child under 18 years old is a protected child, Where this is stated in Law Number 35 of 2014 concerning child protection, and in article 54 paragraph (1) of Law Number 35 of 2014 states that “children in the education unit environment must receive protection from acts of physical, psychological violence, sexual crimes, and other crimes committed by educators, educators, fellow students and or other parties.